Césarienne en urgence au Centre Hospitalier et Universitaire de Brazzaville - Mbongo, Jean Alfred; Butoyi, JM; Papandi-Ikourou, A; Iloki, LH (HEALTH SCIENCES AND DISEASE, 2016)
ABSTRACT OBJECTIVE: To determine the influence of obstetric and surgical practices on the fetal and maternal prognosis. Patients and methods: the study was carried over a period of 6 months collecting retrospective data’s. Extremely urgent caesarean section (C/S), urgent C/S, and the elective ones were included in the study. Women with uterine rupture and those referred for post operative complications following C/S were excluded. RESULTS: 249 C/S have been performed out of 1385 deliveries, giving a global C/S rate of 17.9%. There were 67.5% of Emergency C/S and 32.5% of elective C/S. The average age was 26.3±6 .8 years. Factors associated with poor fetal and maternal prognosis were: the delay between the decision and the execution of the C/S, patients who have been transferred, general anaesthesia, acute foetal distress, placenta praevia, feto-pelvic disproportion. Emergency caesareans were 2.46 times more likely to lead to complications for the mother and 6.03 times more likely to lead to foetal death compared with elective caesarean section. CONCLUSION: The mother and fetal prognosis for emergency C/S was poorer than elective C/S at Brazzaville University Hospital. The medical practice is not yet satisfactory. KEY WORDS: Emergency caesarean section; Brazzaville-Congo. RÉSUMÉ OBJECTIF : Rechercher l’influence respective des facteurs obstétricaux et opératoires sur le pronostic maternel et fœtal. PATIENTES ET MÉTHODES : Il s’agit d’une étude cas témoins, à recueil de données rétrospectif, sur une période de six (6) mois. Ont été inclus les césariennes d’extrême urgence, urgentes, et décidées au cours du travail. La rupture utérine, les patientes référées pour la prise en charge des complications de césarienne, ont été exclues. RÉSULTATS : Sur 1385 accouchements, 249 césariennes ont été réalisées, soit un taux global de césarienne à 17,9 %. Le taux de césariennes en urgence a été de 67,5% de l’ensemble des césariennes contre 32,5% de césariennes non urgentes. L’âge moyen était de 26,3 ± 6,8 ans. Les facteurs aggravant le pronostic maternel et fœtal ont été : le retard entre l’indication et l’exécution de la césarienne, les patientes évacuées, l’anesthésie générale, certaines indications de la césarienne telle que la souffrance fœtale aigue, le placenta prævia, la disproportion fœto-pelvienne. Les césariennes en urgence courent un risque 2,46 fois plus élevé de complications maternelles et 6,03 fois de décès fœtaux que les non urgentes. CONCLUSION : Le pronostic maternel et fœtal des césariennes en urgence est plus sombre que celui des césariennes non urgentes au CHU de Brazzaville. En effet, la pratique médicale en cas d’urgence n’y est pas encore satisfaisante